Engineered exosomes as drug and RNA co-delivery system: new hope for enhanced therapeutics? - Chen, Haorong; Yao, Hanbo; Chi, Jiaxin; Li, Chaowei; Liu, Yilin; Yang, Jiayi; Yu, Jiaqi; Wang, Jiajun; Ruan, Yongdui; Pi, Jiang; Xu, Jun-Fa (Frontiers in Bioengineering and Biotechnology, 2023)
Chemotherapy often faces some obstacles such as low targeting effects and drug resistance, which introduce the low therapeutic efficiency and strong side effects. Recent advances in nanotechnology allows the use of novel nanosystems for targeted drug delivery, although the chemically synthesized nanomaterials always show unexpected low biocompability.The emergence of exosome research has offered a better understanding of disease treatment and created novel opportunities for developing effective drug delivery systems with high biocompability. Moreover, RNA interference has emerged as a promising strategy for disease treatments by selectively knocking down or overexpressing specific genes, which allows new possibilities to directly control cell signaling events or drug resistance.Recently, more and more interests have been paid to develop optimal delivery nanosystems with high efficiency and high biocompability for drug and functional RNA co-delivery to achieve enhanced chemotherapy. In light of the challenges for developing drug and RNA co-delivery system, exosomes have been found to show very attractive prospects. This review aims to explore current technologies and challenges in the use of exosomes as drug and RNA co-delivery system with a focus on the emerging trends and issues associated with their further applications, which may contribute to the accelerated developments of exosome-based theraputics